The Maize Genome (Compendium of Plant Genomes,, 2018)
This book discusses advances in our understanding of the structure and function of the maize genome since publication of the original B73 reference genome in 2009, and the progress in translating this knowledge into basic biology and trait improvement. Maize is an extremely important crop, providing a large proportion of the world's human caloric intake and animal feed, and serving as a model species for basic and applied research. The exceptionally high level of genetic diversity within maize presents opportunities and challenges in all aspects of maize genetics, from sequencing and genotyping to linking genotypes to phenotypes. Topics covered in this timely book range from (i) genome sequencing and genotyping techniques, (ii) genome features such as centromeres and epigenetic regulation, (iii) tools and resources available for trait genomics, to (iv) applications of allele mining and genomics-assisted breeding. This book is a valuable resource for researchers and students interested in maize genetics and genomics.